Peranan Media Pembelajaran dalam jaringan ( DARING ) pada era COVID - 19 bagi Siswa SMA Kota Palembang - Triesia, Diah (JATISI, 2024)
The government is making various efforts to break the chain of spread of COVID-19 by implementing Large-Scale Social Restrictions (PSBB) in every region in Indonesia so that any activities carried out must be online (DARING). In an era of highly developed technology like this, there are lots of online learning media that can be used to assist the teaching and learning process. What's more, some high school students already understand technology, so it's not so difficult to implement learning using online media, and not a few students. Senior High School students who have not been able to do online learning, both due to limited knowledge about technology and limited infrastructure facilities. In this study using quantitative methods in data collection while in data processing using SEM (Structural Equation Model). This study has 16 outliers and has obtained data that are categorized as outliers that have a value of more than a Z-score ≥ 3.0. The results of the questionnaire that has been filled in by existing respondents, the questionnaire statements are all valid with a value of r>.25. It is hoped that the results of this research will become a benchmark in the development of the DARING learning system to make it even better so as to facilitate the learning and teaching process carried out through the online (DARING) network.